Lymph Node Positivity in One-Step Nucleic Acid Amplification is a Prognostic Factor for Postoperative Cancer Recurrence in Patients with Stage II Colorectal Cancer: A Prospective, Multicenter Study - Itabashi, Michio; Yamamoto, Hirofumi; Tomita, Naohiro; Inomata, Masafumi; Murata, Kohei; Hayashi, Shigeoki; Miyake, Yasuhiro; Igarashi, Seiji; Kato, Takeshi; Noura, Shingo; Furuhata, Tomohisa; Ozawa, Heita; et al. (Annals of surgical oncology, 2020)
Background For colorectal cancer (CRC) patients, the standard histological lymph node (LN) evaluation has low sensitivity. Our previously developed one-step nucleic acid amplification (OSNA™) assay measures cytokeratin 19 gene expression in whole LNs. We recently showed that 17.6% of pN0 stage II CRC patients were OSNA positive, suggesting a correlation between OSNA results and disease recurrence. This multicenter, prospective study investigateed the prognostic value of the OSNA assay for pStage II CRC patients. Methods We examined 204 CRC patients who were preoperatively diagnosed as cN0 and cN1 and surgically treated at 11 medical institutions across Japan. Nine patients were excluded, and 195 patients (Stage I: n = 50, Stage II: n = 70, Stage III: n = 75) were examined. All LNs, harvested from patients, were examined histopathologically using one-slice hematoxylin–eosin staining. Furthermore, half of the LNs was examined by the OSNA assay. Patients were classified according to the UICC staging criteria and OSNA results, and the 3-year, disease-free survival (DFS) of each cohort was analyzed. Results Average 21.2 LNs/patient were subject to pathological examination. Approximately half of all harvested LNs (average, 9.4 LNs/patient) were suitable for the OSNA assay. Significantly lower 3-year DFS rates were observed in pStage (pathological Stage) II OSNA-positive patients than in OSNA-negative patients ( p = 0.005). Among all assessed clinical and pathological parameters, only the OSNA result significantly affected 3-year DFS rates in pStage II CRC patients ( p = 0.027). Conclusions This study shows that OSNA positivity is a risk factor for recurrence of the patients with pStage II CRC.